El proceso de conformación de la religiosidad en la Murcia bajomedieval: devociones, cofradías y procesiones - Frey Sánchez, Antonio Vicente (Hispania sacra, 2024)
This paper explains the steps followed in the formation of popular religiosity and its manifestations in the city of Murcia since its incorporation into the Crown of Castilla between 1243 and 1266 and the end of the Middle Ages, from the documentary references of the council records and cathedral archive. It explains how this process was developed following these steps: foundation and endowment of the Cartagena`s Diocese and its fundamental milestones; seat of religious orders, foundation of parishes and subsequent development of a primitive devotional fabric; first manifestations of popular fervor in the form of liturgical and parish processions; foundation of brotherhoods to articulate these manifestations; and, final foundation of labor and guilder brotherhoods. Each and every step was encouraged and promoted frequently by the authorities.